2019
DOI: 10.1108/jima-06-2019-0123
|View full text |Cite
|
Sign up to set email alerts
|

Islamic bank selection criteria in Nigeria: a model development

Abstract: Purpose The purpose of this study is to develop a model for the study of Islamic bank choice and to test the significant importance of the constructs that influence bank customers to choose Islamic bank in a pluralistic-secular nation. Design/methodology/approach Total of 348 conventional and Islamic bank customers were sampled. Five-point Likert-type question containing 27 bank selection items was used in collecting primary data. Cronbach’s alpha, composite reliability and average variance extracted are use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Customers' positive attitudes play a significant role in any bank's success, and this attitude helps attract a new customers for banking transactions [2][3][4][5][6][7][8][9][10][11]. This is also true for Islamic banks.…”
Section: Mediating Effect Of Attitudementioning
confidence: 99%
See 1 more Smart Citation
“…Customers' positive attitudes play a significant role in any bank's success, and this attitude helps attract a new customers for banking transactions [2][3][4][5][6][7][8][9][10][11]. This is also true for Islamic banks.…”
Section: Mediating Effect Of Attitudementioning
confidence: 99%
“…Islamic banks should not be mainly concerned with price competition in this regard. More customers would patronise Islamic banks if they promoted more ethical principles [6]. According to Hadi and Muwazir [7], Islamic banks should priorities both aspects.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study of banking behavior in Indonesia showed that it is necessary for Islamic banks to implement more comfortable waiting areas with more comfortable seats (Aisyah, 2018). Although some studies have reported that customers were satisfied with most of the physical aspects of Islamic banks, such as their internal layout, the suitability of the furniture and their architectural designs, it has been shown that these factors are not the main factors that have significant influence in customers choosing an Islamic bank (Dusuki and Abdullah, 2007;Ezeh and Nkamnebe, 2019). The results suggest that the pull factors of Islamic banks are low enough that there is no incentive for Muslim customers to switch banks.…”
Section: Push and Pull Factormentioning
confidence: 99%
“…As seen in the Table 1, many studies have been conducted in different Islamic geographies in the world to evaluate PBs. In these previous studies, researchers mostly focused on the bank selection criteria (Abdul Hadi and Muwazir, 2020; Awan and Shahzad Bukhari, 2011; Ezeh and Nkamnebe, 2020; Mansour, 2019; Mehar et al , 2019; Rusydiana and Hasib, 2019; Tesfaye et al , 2019) of PB clients. Besides, some authors (Hosen et al , 2021) researched the service quality perceptions of PB clients.…”
Section: Introductionmentioning
confidence: 99%